Liquid Biopsy for Uveal Melanoma. Does It Make Sense? - V. E. Ovanesyan; V. G. Likhvantseva; S. I. Rychkova; S. A. Selkov (Oftalʹmologiâ, 2022)
Purpose: to study the informativeness and appropriateness of liquid biopsy in uveal melanoma (UM).Material and methods. Performed a liquid biopsy (synonym: vitreous fluid biopsy, CST) of enucleated eyes with UM. CST samples were used to quantify the concentration of pro-(IL-8, angiogenin, TNF-α, VEGF, bFGF) and antiangiogenic (IFN-α, TGF-β, IFN-γ) growth factors by multiplex flow cytometry. Compared with the indicators of patients with senile cataracts.Results. Liquid biopsy provided valuable and reliable information about the spectrum of cytokines and their quantitative indicators in the CTZ of the eyes with UM. Compared with senile cataracts in the vitreous fluid of the eyes with UM, there was a significant increase in the frequency of detection and level of proangiogenic cytokines TNF-α (80.0 % vs. 47.5 %, p < 0.05; Msr ± m: 4.3 ± 1.1 pg/ml against 1.4 ± 0.3 pg/ml, p < 0.05), IL-8 (100 % vs. 75 %, p < 0.01; 323.2 ± 227.9 pg/ml versus 8.5 ± 1.5 pg/ml, r < 0.001), angiogenin (11704.9 ± 1767.7 pg/ml versus 2820.15 ± 1404.90 pg/ml, r < 0.01), VEGF (100.0 % vs. 68.2 %; p < 0.05; 471.49 ± 154.60 pg/ml vs. 18.4 ± 3.2 pg/ml, p < 0.05; 471.49 ± 154.60 pg/ml vs. 18.4 ± 3.2 pg/ml, p < 0.05) and bFGF (60.0 % vs. 26.7 %, p < 0.05; Msr: 44.6 ± 16.2 vs. 2.7 ± 1.0, p < 0.001). In both groups of patients, the antiangiogenic factor TGF-β was not detected, but the concentration of IFN-γ was found in five of the eight samples at the level of 14.9 ± 12.2 pg/ml, and the levels of IFN were 4 times higher: 17.6 ± 3.9 pg/ml against 4.4 ± 0.4 pg/ml (p < 0.05).Conclusions. Liquid eye biopsy with UM using multiplex flow cytometry can be a valuable and highly informative tool for studying UM phenotypes, in the development and selection of molecular targets for antiangiogenic or other targeted therapies. Elevated levels of proangiogenic growth factors (IL-8, angiogenin, TNF-α, VEGF and bFGF) in vitreous fluid in UM indicate the presence simultaneously of three mechanisms for stimulating angiogenesis, two of which are independent of VEGF, act independently, and may show synergism. Insufficiently high levels of interferons (IFN-γ and IFN-α) against the background of the absence of TGF-β in the vitreous fluid allow us to think that the secretion and control of the regulation of the natural angiostatic link of angiogenesis in the eyes with choroidal melanoma is suppressed. High levels of cytokines with pluripotent (proangiogenic and pro-inflammatory) properties indicate that in choroidal tumors, inflammation may play the role of a promoter of angiogenesis.